Ganges theory of change workshop report - Bayot, Ruvicyn S.; Salahuddin, A.; Douthwaite, Boru (2011)
If research is to have an impact then people must use the outputs, knowledge and insights it generates. This means that researchers and their organizations must link to next users and end users of their research. What a project or program does and who it does with to achieve impact is called its Theory of Change (ToC). Programs with clear and plausible ToC are more likely to be supported, more likely to achieve impact, and easier to monitor. This workshop will introduce participants to Participatory Impact Pathways Analysis (PIPA) as a way of articulating ToC, and using it in program planning and monitoring.